Synthesis and Evaluation of Some Novel Benzimidazole Derivatives Bearing Thiazolidinone Moiety as Potential Antimicrobial Activity - Sudhir Kumar1, P.; Patro2, S.K. (Asian Journal of Chemistry, 2013)
A new series 3-(3-hydroxy-4-(1H-benzo[d]imidazol-2-yl)phenyl)-2-substituted phenylthiazolidin-4-one (4a-h) were synthesized by the cycloaddition of 2-(benzo[d]imidazol-2-yl)-5-(4-substituted benzylideneamino)phenol (3a-h) with thioglycollic acid in the presence of anhydrous zinc chloride in 1,4 dioxane and the compounds (4a-h) further coupled with diazonium salt of sulphonilamide to give diazo substituted of thiazolidinone. The structures of these newly synthesized were characterized by elementary analysis, IR, 1H NMR and the synthesized compounds were evaluated in vitro for their preliminary antibacterial activity against various bacterial viz: E. coli, S. aureas, S. typhi and Pseudomonas species and of their antifungal activities versus Aspergillus niger and Aspergillus oryzae. Antibacterial and antifungal activities of each compound were compared with standards amoxicillin and fluconazole, respectively. The results revealed that some compounds were exhibited moderate to good antibacterial activity against both Gram (+) and Gram (-) bacteria whereas same compounds were exhibited moderate to weak antifungal action against both fungal strains.